Using SomaticSniper to Detect Somatic Single Nucleotide Variants. Issue 1 (21st March 2014) - Larson, David E.; Abbott, Travis E.; Wilson, Richard K.
Abstract: Detecting somatic single nucleotide variants (SNVs) is an essential component of cancer research with next‐generation sequencing data. This unit describes how to run the SomaticSniper somatic SNV detector and then filter the output to eliminate most false positives. It also includes support protocols detailing the compilation of the software. Curr. Protoc. Bioinform . 45:15.5.1‐15.5.8. © 2014 by John Wiley & Sons, Inc.